Teachers’ Experiences on Refugee Education and Their Views on Refugees’ Social Inclusion: Case of Turkey - Topaloğlu, Hakan; Özdemir, Murat (Alberta Journal of Educational Research, 2023)
This study had two aims: first, to reveal the experiences of educators who work with refugee students in Samsun (Turkey); and second, to divulge the views these teachers have on the social inclusion of refugees. The research was designed using a case study approach; 18 individuals participated in the research, who were selected from 12 schools within the criterion sample. A semi-structured interview form was utilized to collect data, which were analyzed using a content analysis approach. Some participants indicated that some refugee students were indifferent toward their lessons, would act in violent ways at school, experienced academic inadequacies, and possessed language and communication issues. Other teacher-participants pointed out that refugee students suffered from discrimination at school. In a general sense, the participants had a positive attitude towards refugee social inclusion, and they believed that refugees should be given employment opportunities; but refugees should also learn about Turkish culture and values. The study concluded that an equal distribution of refugees across schools and residential areas is necessary and that organizing events where refugees and Turkish citizens can join together provides the whole society with opportunities to learn about multiculturalism, which in turn can accelerate social inclusion. Keywords: Refugee, immigrant, social inclusion, discrimination, access to education. Cette étude avait deux objectifs : premièrement, révéler les expériences des éducateurs qui travaillent avec des étudiants réfugiés à Samsun (Turquie) ; et deuxièmement, rendre compte des points de vue de ces enseignants sur l'inclusion sociale des réfugiés. La recherche a été conçue selon une approche d'étude de cas ; 18 personnes ont participé à la recherche et ont été sélectionnées dans 12 écoles de l'échantillon de référence. Un formulaire d'entrevue semi-structurée a été utilisé pour collecter les données, qui ont été analysées à l'aide d'une méthode d'analyse de contenu. Certains participants ont indiqué que certains étudiants réfugiés étaient indifférents à leurs cours, agissaient de manière violente à l'école, présentaient des lacunes scolaires et avaient des problèmes de langue et de communication. D'autres enseignants-participants ont souligné que les étudiants réfugiés souffraient de discrimination à l'école. D'une manière générale, les participants avaient une attitude positive à l'égard de l'inclusion sociale des réfugiés, et ils pensaient qu’on devrait offrir aux réfugiés des possibilités d'emploi, mais que ceux-ci devaient aussi apprendre la culture et les valeurs turques. L'étude conclut qu'une répartition égale des réfugiés dans les écoles et les zones résidentielles est nécessaire et que l'organisation d'événements où les réfugiés et les citoyens turcs peuvent se rencontrer donne à l'ensemble de la société l'occasion d'apprendre le multiculturalisme, ce qui à son tour peut accélérer l'inclusion sociale. Mots clés : réfugié, immigrant, inclusion sociale, discrimination, accès à l'éducation.